Advanced polytopic projects - Iordache, Octavian (Switzerland : Springer, 2019)
This book focuses on new developments in polytopic projects, particularly on implementation domains and case studies, as well as high-dimensional methodology. Polytopic projects are based on a general reference architecture inspired and shared by the functional organization of organisms and enterprises as informational and cognitive systems, the scientific and engineering methodology and the operational structure of existing self-evolvable and self-sustainable systems.
Tambien disponible en formato EPUB
Keywords: INTELIGENCIA COMPUTACIONAL; SISTEMAS DE AUTOORGANIZACIÓN; POLITOPOS; DISEÑO EN INGENIERÍA; CONTROL AUTOMÁTICO